2009
DOI: 10.1111/j.1523-536x.2009.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

A Birth Education Program for Expectant Fathers in Taiwan: Effects on Their Anxiety

Abstract: The study findings justify the clinical implementation of a birth education program based on the self-efficacy theory as an effective means of reducing anxiety among expectant fathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 38 publications
4
43
0
8
Order By: Relevance
“…Moreover, a lower percentage of fathers prepared for labor experience negative emotions, such as anxiety, irritation and fear, which is another benefit resulting from ante-natal education. The results of Li HT et al confirm this hypothesis [9].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, a lower percentage of fathers prepared for labor experience negative emotions, such as anxiety, irritation and fear, which is another benefit resulting from ante-natal education. The results of Li HT et al confirm this hypothesis [9].…”
Section: Discussionsupporting
confidence: 82%
“…The author's own studies are consistent with those reported by other authors and confirm that fathers actively participate in childbirth and women have specific preferences concerning this issue [9,11,[17][18][19]. Paternal activity in individual stages of labor mostly involves emotional support for the woman in labor, but also performing nursing activities and instrumental monitoring.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Stress management, lifestyle changes and the recognition of increased relationship strain are not mandatory within the antenatal program and can be completely omitted [63]. Corroborating the experience of the men in our study, a systematic review of antenatal education found that men valued access to experienced fathers and the opportunity to discuss their own concerns and learn strategies for coping with anxiety [64] The importance of information to reduce confusion and giving fathers an opportunity to explore their new roles has been identified in several studies [65,66]. …”
Section: Discussionmentioning
confidence: 79%
“…The amendment of education level, the reference of delivery information and delivery expectations, along with attendance in the classes, and delivery--based education can significantly decrease the level of anxiety in fathers after birth. According to this study, the clinical implementation of prenatal educational courses based on the self--efficacy theory is an effective strategy to reduce anxiety among fathers [28]. According to the investigations, fathers often feel worried in terms of the infant's health, such as the risk of having children with disabilities, but they often feel anxiety in terms of their supportive role regarding their pregnant wives [29][30][31].…”
Section: Resultsmentioning
confidence: 98%